2020
DOI: 10.24989/dp.v1i2.1867
|View full text |Cite
|
Sign up to set email alerts
|

Teletherapy for Adolescent Psychiatric Outpatients: The Soaring Flight of so far Idle Technologies during the COVID-19 Pandemic

Abstract: Owed to the COVID-19 pandemic, teletherapeutic offers skyrocketed, in the need of the moment seemingly faster that the background technology and training could be provided. This spotlight communication gives an overview of results and ideas on teletherapeutic offers for adolescent psychiatric outpatients and impulses for further investigations. We report insight gained from following up 30 adolescents in weekly outpatient treatment on an interview basis. Therapists’ views were collected via informal discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
7
6
0
3
Order By: Relevance
“…They experienced sessions to be more superficial and described a tendency to talk and avoid silences in patients and in themselves. These results are consistent with those of Huscsava et al (2020), who suggested that therapeutic processes become more superficial in remote psychotherapy. However, in the psychoanalytically oriented debate, a number of authors pointed out that these dynamics may be understood as defenses on the parts of both patient and therapist and need to be analyzed and addressed as such in therapy (Scharff, 2012;Migone, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…They experienced sessions to be more superficial and described a tendency to talk and avoid silences in patients and in themselves. These results are consistent with those of Huscsava et al (2020), who suggested that therapeutic processes become more superficial in remote psychotherapy. However, in the psychoanalytically oriented debate, a number of authors pointed out that these dynamics may be understood as defenses on the parts of both patient and therapist and need to be analyzed and addressed as such in therapy (Scharff, 2012;Migone, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…A more specific analysis of different aspects of the psychotherapeutic encounter revealed that transference/countertransference processes, the intensity and the therapeutic process change the most. This is supported by previous studies, revealing that remote sessions were experienced to be more superficial [27]. Specific therapeutic interventions were also rated to be more typical in in-person settings as compared to remote settings [28].…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with our previous study, psychotherapists rated psychotherapy via the internet more comparably to in-person psychotherapy than to psychotherapy via telephone [4]. However, previous research has revealed that remote sessions are experienced as being more superficial than inperson sessions [21] and specific therapeutic interventions have also been rated to be more typical in in-person settings as compared to remote settings by therapists [10]. Thus, aspects other than the three investigated variables likely contributed to the increased utilization of in-person psychotherapy compared to psychotherapy via the internet.…”
Section: Discussionsupporting
confidence: 87%